Media representation of Iraq in the American press during the nineteenth century - Hadad, Dr. Hussein Ismaeel (Thi Qar Arts Journal, 2024)
The current research deals with the media representation of Iraq in the American press during the nineteenth century. An analytical sample consisting of 141 articles and news items for various newspapers was selected for a period of time extending from 1850 to 1900, representing the nineteenth century press in the United States of America. The research aims to reveal the characteristics of media representation. For Iraq during that period, the most prominent trends were the American press discourse in approaching Iraqi issues and its reflection on the mental image of the recipient. For this purpose, a mixed methodology of quantitative and qualitative analysis was used, represented by the method of content analysis and qualitative thematic analysis, for the purpose of revealing the most prominent characteristics of the media representation of Iraq during that period in which it was under Ottoman occupation, in addition to employing Orientalist discourse as a theoretical structure upon which the research was based in demonstrating and interpreting the dimensions of representation. Media figures for Iraq in the American press during the period studied. The most prominent findings of the research were that the historical dimension was prevalent in the process of media representation when dealing with Iraqi issues, and that the Orientalist discourse is present in the view of American writers towards Iraq and its cities and does not deviate from the duality of opposition that this discourse focuses on between the West and the East.